Concepções de linguagem e perspectivas pedagógicas no ensino de Inglês em contexto de formação e implementação curricular na Rede Pública Municipal de São Paulo - Lopes, Maurício José Ferreira (2019)
This research had as general objective to investigate how the conceptions of language of English teachers of the São Paulo Municipal Board of Education are linked to questions about what and how to teach in their pedagogical practices. Its specific objectives are: 1) to identify implicit or explicit language conceptions in the discourses produced by the participating teachers and the teacher-researcher throughout a curricular training and implementation course; 2) to reflect on the implications of these conceptions of language, emerging in such discourses in the light of the conceptions proposed by Curriculum of the City of São Paulo (2017), regarding the curricular component of English Language. Two research questions guide the work, namely: 1) what conceptions of language emerge from the teachers' speech throughout a course of curricular implementation and to which concepts of teaching and learning of English are such conceptions linked? 2) How is the question of the conception of language treated in the last two curricular documents of English Language teaching, of the São Paulo Municipal Board of Education? It is, therefore, a qualitative research of an interpretative nature, divided in two parts, being an ethnographic and another documentary, pointing in this way, to a critical view (DENZIN & LINCOLN, 2008). Thinking about the relationship between language conceptions, pedagogical practices and curricular guidelines of EL can contribute not only to a more meaningful teaching for the learner but is also a sine qua non condition to the comprehension and adherence to the pedagogical perspectives of Multiliteracies. The survey revealed that about 25% of teachers (those with a postgraduate degree in language teaching) of EL are guided by a conception of language as social practice or social construction. The majority of English teachers still focus on teaching the system or on linguistic and grammatical aspects. Difficulties in understanding a conception of language as a social practice are reflected in the low adherence to pedagogical proposals that focus on the language in use. The study of curricular documents reveals that the question of the language conceptions involves a political dispute instead of being a purely theoretical-methodological question